國民小學師資培育「國音及說話」課程內容與實施現況分析 - 張金蘭, 張金蘭 (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2022)
對教師而言，口語是傳達教學內容的重要媒介。在臺灣的國小師資培育課程中，與教師口語表達緊密相關的重要課程為「國音及說話」，其亦為師資生「教學基本學科課程」與各科教材教法的先修課程，足見此課程之重要性。本文研究目的在瞭解「國音及說話」課程內容與實施，故以課程大綱與授課教師為研究對象，探討此課程的課程目標、課程內容、授課方法與評量方式。首先由教育部大學校院課程資源網查詢106到110年，共計五個學年度、294門「國音及說話」課程，刪去重覆教師與課程大綱不完整者，共計44門。研究採取內容分析法分析課綱，並根據文獻探討與課程大綱分析結果做為擬定訪談題綱的基礎，而後訪談8位授課教師，最後比對與分析所得資料並提出結論。研究結果有四，一是課程目標兼顧國音理論與說話實務；二是課程內容重國音理論、輕說話實務；三是授課方法多採取教師講授國音理論、師資生練習說話實務的方式進行，但因修課人數過多、授課時數不足之故，導致實務練習不足；四是在評量方式上，多以紙筆測驗來評量國音理論知識，以口語練習或測試來評量說話能力，但口試未有相關標準與方式。研究者將針對此研究結果提出相關建議，並希望此研究能提供國小師資培育大學開設「國音及說話」課程的參考。 For teachers, oral language is an important medium for conveying teaching content. In Taiwan’s elementary school teacher training courses, the compulsory course closely related to teachers’ oral expression is "Chinese Phonology and Speech". This study aimed to understand the content and implementation of the "Chinese Phonology and Speech" course in such training and took. the curriculum syllabus and teachers as the research objects to discusses the curriculum objectives, content, teaching methods and evaluation methods. First, the Ministry of Education’s "University and College Course Information website" investigated the "Chinese Phonology and Speech" courses for five academic years from 2017 to2021. In total, forty-four courses, with repeated teachers and incomplete syllabus, were deleted. This research adopted the content analysis method to analyze the syllabus. Based on the literature discussion and syllabus analysis results for setting up the interview questions, it then conducted interviews with eight teachers. There were four research results. First, the curriculum objectives took into account both the theory of the national accent and the practice of speaking. Second, the course content emphasizes the theory of the national accent and neglects the practice of speaking. Third, students practice speaking in a practical way, but because the number of students in a class i too large and the number of teaching hours was insufficient, they still feel that the practical practice i insufficient. Fourth, in terms of assessment methods, paper and pencil tests were often used to evaluate teachers and students' national pronunciation theoretical knowledge, while the speaking abilities of teachers and students were assessed by oral practice or tests. There were no relevant standards and methods for the oral tests. This study puts forward relevant suggestions based on the results herein so as to provide a reference for the "Chinese Phonology and Speech" courses offered by elementary school teacher training universities.